A preliminary investigation of the contribution of different tenderness factors to beef loin, tri-tip and heel tenderness. (December 2020) - Chun, C.K.Y.; Wu, W.; Welter, A.A.; O'Quinn, T.G.; Magnin-Bissel, G.; Boyle, D.L.; Chao, M.D.
Abstract: The objective of this study was to identify the relative contribution of tenderness factors for three beef muscles with similar tenderness ratings. Longissimus lumborum (LL), tensor fascia latae (TF) and gastrocnemius (GC) were collected from 10 USDA low Choice beef carcasses and assigned to a 5 or 21 days aging period ( n = 60). Sarcomere length, troponin-T degradation, collagen content, mature collagen crosslink density, intramuscular lipid content and trained panel analysis were measured. Correlation and multivariate regression analysis indicated each muscle has a specific tenderness factor that contributed to the overall tenderness evaluated by trained panelists. The equations indicated LL tenderness was driven by lipid content ( P < .05); TF tenderness was driven by collagen content ( P < .05). GC tenderness was driven by proteolysis ( P < .01), and only collagen content can be casually used as an overall tenderness predictor for all three cuts.